Peningkatan Hasil Belajar IPA Siswa Kelas 1 Tentang Benda-Benda Langit Melalui Model Pembelajaran Direct Instruction di SDN Kebagusan 05 Petang Pasar Minggu Jakarta Selatan - Maryatih, Maryatih; Hermawan, Cecep Maman; Rosfiani, Okta; Rachmawati, Anida; Jalalludin, Imam; Aulia, Muhammad Hanif (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The purpose of the study was to improve student learning outcomes, therefore researchers applied the Direct Instruction model in science education which was applied to grade 1 SDN Kebagusan 05. The problem in this study is the low academic achievement of students in grade 1 of SDN Kebagusan 05 Pasar Minggu District in the Field of Natural Sciences. One of the factors causing low student ability is that the learning model used tends to make students passive and less interested. This research is a classroom action research using a cycle system, where each cycle consists of four stages with a total of 31 students, each cycle consists of intervention planning, implementation, observation and reflection. From the results of the first cycle activities, 21 students obtained more than 65 points or 67.7% of 31 students, while 10 students obtained less than 65 points or 32.3% of 31 students. The results of the second cycle operation showed that 29 students or 93.5% of 31 students obtained grades above 65 students, while 2 students obtained grades below 65 points or 6.5% of 31 students. Thus, it can be concluded that the application of the Direct Instruction model can improve the learning outcomes of grade 1 students of SDN Kebagusan 05. The purpose of the study was to improve student learning outcomes, therefore researchers applied the Direct Instruction model in science education which was applied to grade 1 SDN Kebagusan 05. The problem in this study is the low academic achievement of students in grade 1 of SDN Kebagusan 05 Pasar Minggu District in the Field of Natural Sciences. One of the factors causing low student ability is that the learning model used tends to make students passive and less interested. This research is a classroom action research using a cycle system, where each cycle consists of four stages with a total of 31 students, each cycle consists of intervention planning, implementation, observation and reflection. From the results of the first cycle activities, 21 students obtained more than 65 points or 67.7% of 31 students, while 10 students obtained less than 65 points or 32.3% of 31 students. The results of the second cycle operation showed that 29 students or 93.5% of 31 students obtained grades above 65 students, while 2 students obtained grades below 65 points or 6.5% of 31 students. Thus, it can be concluded that the application of the Direct Instruction model can improve the learning outcomes of grade 1 students of SDN Kebagusan 05.